A solid-state microwave method to disrupt biomass microstructure for natural product extraction - See, Tiam You; Yusoff, Rozita; Chan, Chung-Hung; Ngoh, Gek Cheng (Elsevier, 2018)
This paper introduces an innovative solid-state microwave disruption (SSMD) method for the extraction of bioactive materials from plants. It is an alternative method that avoids the use of solvents for plant biomass sample pretreatment unlike those in the conventional microwave methods. SSMD method is preferred since the heating and the vaporization of the intracellular moisture within the plant biomass is able to create sufficient pressure to disrupt the biomass microstructure. In this work, the superiority of the SSMD method was validated using the bioactive extraction from Orthosiphon stamineus (Java tea) leaves. First, the degree of disruption of SSMD method under the effects of microwave power and heating time were investigated at various up-scaled conditions based on the structural analysis of the treated sample, and the extraction yields of the bioactive compounds after soaking and elution with a suitable solvent at room conditions. The results show that the SSMD-elution method gave a better extraction yield (4.65 ± 0.08 mg/g), which is comparable to that of microwave-assisted extraction (4.45 ± 0.03 mg/g) and ultrasonic-assisted extraction (4.18 ± 0.02 mg/g). In addition, this method has great operational simplicity and flexibility in terms of operating parameters, types of solvent and solvent consumption.